2022
DOI: 10.1039/d2ta03154j
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Eu@HOF luminescent fabric as a highly selective and sensitive optical synapse sensor for identification of six laboratory volatile compounds by neuromorphic computing

Abstract: As the product of artificial intelligence (AI) age, artificial optical synaptic sensor (AOSS) integrating optical sensor and artificial synaptic system (ASS) performs the huge advantage for classification and quantitative detection...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 70 publications
0
19
0
Order By: Relevance
“…PXRD reveals that the structure of IsoMe in the Eu 3+ @IsoMe fabric is retained well. 124 Xu et al also reported an Eu 3+ functionalized IsoMe hydrogel film. Because of the numerous hydrogen donors and acceptors on IsoMe and AG hydrogels, IsoMe can combine with AG to form an IsoMe@AG hydrogel easily.…”
Section: Fabrication Of Ln@hof Luminescent Materials and Their Devicesmentioning
confidence: 98%
See 1 more Smart Citation
“…PXRD reveals that the structure of IsoMe in the Eu 3+ @IsoMe fabric is retained well. 124 Xu et al also reported an Eu 3+ functionalized IsoMe hydrogel film. Because of the numerous hydrogen donors and acceptors on IsoMe and AG hydrogels, IsoMe can combine with AG to form an IsoMe@AG hydrogel easily.…”
Section: Fabrication Of Ln@hof Luminescent Materials and Their Devicesmentioning
confidence: 98%
“…14 (a) The preparation process from IsoMe to an electrodeposited Eu@IsoMe fabric by coordinated PSM and ED methods. 124 (b) The preparation process of an Eu@IsoMe@AG hydrogel film. 125…”
Section: Conflicts Of Interestmentioning
confidence: 99%
“…20,21 Lanthanide-functionalized hydrogen-bonded organic frameworks (Ln@HOFs), which combine the excellent uorescence properties of Ln 3+ ions with the remarkable advantages of HOFs, show bright prospects in uorescence sensing applications. 22 Several reported Ln@HOFs can effectively sensitize Ln 3+ ions and emit the characteristic uorescence of Ln 3+ ions via ligand-to-metal charge transfer (LMCT). For instance, Cao and coworkers fabricated a Eu@TCBP lm by electrophoretic deposition (EPD) for temperature sensing.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26][27][28] Especially, when combined with intelligent technology, they can not only improve the detection performance, but also be of help to build a multifunctional platform to improve application performance. 24,29,30 Therefore, hydrogen-bonded organic framework (HOF)-based fluorescence sensors have received increased interest owing to their exclusive structure and properties. HOFs are an innovative class of crystalline porous materials, selfassembled from organic building blocks by means of hydrogen bonding interactions and enhanced via van der Waals forces, p-p stacking interactions, electrostatic interactions, etc.…”
mentioning
confidence: 99%
“…23,[39][40][41][42][43] For example, Xu et al fabricated a wearable Eu@HOF luminescent fabric with dual-emitting centers for ratiometric detection of harmful gases. 30 Cao and co-workers prepared a lanthanidefunctionalized HOF film by electrophoretic deposition to monitor temperature. 39 It is intuitively known that post-synthetic modification (PSM) has become an emerging strategy to incorporate exogenous functional species into HOFs, endowing HOFs with new physical and chemical properties.…”
mentioning
confidence: 99%